TEKNOLOGI PENYAMBUNGAN (GRAFTING) MENDUKUNG PENGEMBANGAN, PEREMAJAAN DAN REHABILITASI PERTANAMAN JAMBU METE / Grafting Technology for Support Extensification, Replanting, and Rehabilitation of Cashew Plantation - Rudi Suryadi (Puslitbang Perkebunan, 2018)
Initially cashew cultivation was aimed at marginal land conservation. A tight spacing (3 m x 3 m) so that the crown can cover the ground as quickly as possible to prevent soil erosion during rain and deciduous cashew leaves will add soil organic matter. Therefore aspects of plant productivity have not been a concern. As the price of cashew nuts tends to increase every year. This can encourage farmers to try cashew crops more seriously. At present, cashew cultivation is not only an effort to conserve marginal land, but also as a source of income for farmers, especially in Eastern Indonesia (KTI). Until 2016, Indonesia's cashew area had reached 514,491 ha with production of 137,094 tons. However, the level of productivity is considered still low, namely 430 kg logs/ha/year, far below India and Nigeria in the range of 900-2,286 kg logs/ha/year. Some factors that cause low productivity of Indonesian cashew are (1) the quality of plant material used, (2) disruption of pests and diseases, (3) maintenance of plants, and (4) the number of old plants (> 30 years). For this reason, efforts need to be made to increase the productivity of cashew, by implementing grafting technology in the extensification, replanting and rehabilitation of cashew. Research related to the grafting has been done quite a lot and produced, both grafting in nurseries and directly on the field (top working). The production potential of 9 superior varieties released ranged from 5.97 - 37.44 kg logs/trees/year or an average of 16.70 kg logs/trees/year. If the extensification, replanting and rehabilitation activities apply the grafting technology using the stem from superior varieties, it will be able to increase the productivity of Indonesian cashew to 1,670 kg logs/ha/year or increase by 300% from current productivity. AbstrakAwalnya penanaman jambu mete bertujuan untuk konservasi lahan marjinal. Jarak tanam rapat (3 m x 3 m) agar tajuk dapat secepat mungkin menutup permukaan tanah untuk mencegah erosi permukaan tanah saat hujan dan daun jambu mete yang gugur akan menambah bahan organik tanah. Oleh sebab itu aspek produktivitas tanaman belum menjadi perhatian. Seiring perkembangan harga kacang mete cenderung meningkat setiap tahunnya. Hal tersebut mampu mendorong petani untuk mengusahakan tanaman jambu mete lebih serius. Saat ini penanaman jambu mete tidak hanya sebagai usaha konservasi lahan marjinal, namun menjadi sumber pendapatan petani, terutama di Kawasan Timur Indonesia (KTI). Sampai 2016, luas areal mete Indonesia telah mencapai 514.491 ha dengan produksi 137.094 ton. Namun, tingkat produktivitas dianggap masih rendah yaitu 430 kg gelondong/ha/tahun, jauh dibawah India dan Nigeria pada kisaran 900-2.286 kg gelondong/ha/tahun. Beberapa faktor yang menyebabkan rendahnya produktivitas jambu mete Indonesia yaitu (1) mutu bahan tanaman yang digunakan, (2) gangguan hama dan penyakit, (3) pemeliharaan tanaman, dan (4) banyaknya tanaman tua (>30 tahun). Untuk itu perlu ditempuh upaya meningkatkan produktivitas jambu mete, dengan menerapkan teknologi penyambungan pada kegiatan pengembangan, peremajaan dan rehabilitasi pertanaman jambu mete. Penelitian terkait penyambungan sudah cukup banyak dilakukan dan dihasilkan, baik penyambungan di pembibitan maupun langsung di lapang (top working). Potensi produksi dari 9 varietas unggul yang dilepas berkisar antara 5,97- 37,44 kg gelondong/pohon/tahun atau rata-rata 16,70 kg gelondong/pohon/tahun. Apabila kegiatan pengembangan, peremajaan dan rehabilitasi menerapkan teknologi penyambungan menggunakan batang atas dari varietas unggul, akan mampu meningkatkan produktivitas jambu mete Indonesia menjadi 1.670 kg gelondong/ha/tahun atau meningkat 300 % dari produktivitas saat ini.